1990
DOI: 10.1021/jm00165a018
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, conformation, and immunosuppressive activities of three analogs of cyclosporin A modified in the 1-position

Abstract: The syntheses of three new cyclosporin A (CsA) analogues that contain novel MeBmt derivatives in the 1-position are described. The MeBmt analogue that contains an additional methyl group on C4, (2S,3R,6E)-4,4-dimethyl-3-hydroxy-2-(N-methylamino)-6-octenoic acid (MeBm2t), was synthesized in four steps beginning with the reaction of Pmz-Sar-OtBu with (4E)-2,2-dimethyl-4-hexenal. The C4 desmethyl analogue of MeBmt, (2S,3R,6E)-3-hydroxy-2-(N-methylamino)-6-octenoic acid (MeBth), was synthesized in nine steps by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…From this investigation, it was clearly shown that immunosuppressive activity was influenced by a large part of the overall Cs molecule and only a few variations could be installed to increase the activity. A study regarding the CsA 51 conformation in solution has been performed [47]. It was found that the insertion of a polar group always caused the activity to be diminished [46].…”
Section: Biological Activitymentioning
confidence: 99%
“…From this investigation, it was clearly shown that immunosuppressive activity was influenced by a large part of the overall Cs molecule and only a few variations could be installed to increase the activity. A study regarding the CsA 51 conformation in solution has been performed [47]. It was found that the insertion of a polar group always caused the activity to be diminished [46].…”
Section: Biological Activitymentioning
confidence: 99%
“…CsA was kindly provided by Sandoz Pharma LTD, Switzerland. MeBm 2 tl-CsA was synthesized as described [49]. Co-crystals of the CyPA-CsA complex were grown by a two-step procedure: (1) mixing the 16mgml-1 CyPA protein solution from the purification with 10 mM CsA/ethanol in a molecular ratio of 1:2 overnight and (2) crystallizing 13mgml-1 of the complex by dialysis against a buffer containing 20mM Tris-base, 2mM…”
Section: Crystallization and X-ray Data Collectionmentioning
confidence: 99%
“…Unfortunately, in cells both compounds inhibit the PPIase activity of cyclophilins at the nanomolar concentration range and are therefore unsuitable as a monospecific calcineurin inhibitor. Moreover, modifications of residues in the cyclophilin binding region (e.g., MeBmt at position 1) by substitution or elongation of the side chain alter only the cyclophilin inhibition, but impair the immunosuppressive potency only marginally, as observed for wMeBm 2 t 1 x-CsA, wMeBth 1 x-CsA, wMeByt 1 x-CsA and voclosporin (ISA247) (53,54). A completely new regulation mechanism of CsA inhibitory potency was realized with a CsA derivative containing a biotin moiety connected by an azobenzene tether (55).…”
Section: Cyclosporin a (Csa)mentioning
confidence: 99%